CRP/anti-CRP antibodies assembly on the surfaces of cell remnants switches their phagocytic clearance towards inflammation - Janko, Christina; Franz, Sandra; Munoz, Luis E.; Siebig, Stefan; Winkler, Silke; Schett, Georg; Lauber, Kirsten; Sheriff, Ahmed; Van Der Vlag, Johan; Herrmann, Martin (Frontiers in Immunology, 2011)
Systemic Lupus Erythematosus (SLE) is a chronic inflammatory disease characteris¬ed by the production of autoantibodies, formation of immune complexes (IC), and activation of complement that ultimately fuel acute and/or chronic inflammation. Accumulation in blood and tissues of post-apoptotic remnants is considered of etiological and pathological importance for patients with SLE. Besides receptors directly recognising apoptotic cells, soluble opsonins of the innate immune system bind apoptotic material dependent on the stage of apoptosis. We describe the binding to the surface of Secondary NEcrotic Cells (SNEC) of the serum opsonin CRP and further opsonins. We show that anti-dsDNA and anti-CRP autoantibodies bind and opsonise SNEC. These SNEC opsonised with autoantibodies were cleared by macrophages in vitro and induced a pro-inflammatory cytokine response. In conclusion, anti-CRP, CRP and SNEC form a ternary pyrogen endowed with strong pro-inflammatory capabilities which is able to maintain and perpetuate chronic inflammation.